Interpersonal Deception Pengguna Dating Apps Bumble (Universitas 17 Agustus 1945 Surabaya, 2023)
Bumble is an application designed so that people can establish relationships with one another, whether as friends, girlfriends, or potential partners (husband and wife). For this purpose, as with its terms and conditions, Bumble requires that its users share information about themselves correctly. Not a few of its users commit deception, with various purposes. This study aims to explore the forms of lying (interpersonal deception) that occur in Bumble, the motivations that drive them to lie, and the implications of these lies for victims and perpetrators. The theory used in this study is Interpersonal Deception Theory (IDT) introduced by David Buller and Judee Burgoon (1996). The method uses a qualitative exploratory approach. Data was collected through interviews with five Bumble users and analyzed using the interactive model from Miles & Huberman. The results of his research are that both victims and perpetrators lie about their information. Perpetrators tend to cat-fishing and photo manipulation of themselves, flexing, and breadcrumbing behavior. The perpetrator's deception action aims to get the desired partner match. As for victims, deception is done to maintain privacy. Keywords: Interpersonal Deception, Bumble, Dating online